In-situ synthesis of 3D BiOBr/UiO-66-NH2 heterojunction nanocomposite and its excellent photocatalytic degradation of rhodamine B dye - Feng, Shuna; Yan, Zheng; Ni, Qianqian; Zhang, Yun (Frontiers in Environmental Science, 2022)
The fast recombination of stimulated excitons and poor visible light response are key problems in the photocatalysis field. Combining with materials with good visible light responses to form heterogeneous structures is still the most effective way. In this study, BiOBr/UiO-66-NH2 photocatalyst was synthesized by a simple method. BiOBr is a 3D spherical structure stacked by nanosheets, which enhance its adsorption capacity for pollutants and catalyze the dark reaction to reach the equilibrium point for too long. Coupling with UiO-66-NH2, its adsorption capacity was inhibited and the dark reaction time was shortened. The excellent removal rate of Rhodamine B (RhB) by BiOBr/UiO-66-NH2 reached 96.79% after 30 min of visible light irradiation and 99.37% after 90 min. With an increase in pollutant concentration, the composite still showed excellent photocatalytic performance. This study also tried to abandon the dark adsorption stage and directly degraded RhB efficiently and quickly under visible light. Finally, the photocatalytic enhancement mechanism was proposed.